PERLINDUNGAN HUKUM BAGI KONSUMEN PADA LAYANAN PINJAMAN ONLINE (Faculty of Law, University of Palembang, 2022)
Through information technology-based money lending, it makes it easier for people to fulfill cash funds quickly, easily, and efficiently. However, users of this service must understand all the risks of online loans. The operator's obligations in legal protection for consumers are further regulated in OJK Regulation Number: 77/POJK.01/2016 concerning Information Technology-Based Borrowing-Lending Services, then the organizers are required to apply the basic principles of consumer protection, namely: transparency; fair treatment; reliability; data confidentiality and security; and user dispute resolution in a simple, fast, and affordable way.